The Effects of Imported Frozen Food from Thailand on Tumpat Community - RADEN ISMAIL, RADEN MOHD FARHAN HELMY; AZAMI, NUR AIN ASSYIKIN; ROHIAT, MOHD AKMAL (Research and Innovation in Technical and Vocational Education and Training, 2021)
This frozen food has become a must for consumers in this modern world. This is because consumers feel frozen food can ease the burden of work while they are busy. This frozen food is well known for saving time and energy when it comes to preparing food. This frozen food is not only used by the working community but also used by housewives and also as a selling point for merchants. Accordingly, the study was conducted to identify factors, safety and also the effects of frozen food from Thailand on the Tumpat community. Researchers have selected the people of Tumpat to be the population in this study. These residents have been selected to determine the level of acceptance of frozen food from Thailand. Quantitative methodology is used by distributing questionnaire instruments and the data obtained were analyzed and descriptive statistic using Statistical Packages for Social Science (SPSS) version 25.0. From this study it is also found that the Tumpat community as a whole has a high tendency of mean scores on frozen food from Thailand.